Innovative Soluble Silicon Leaf Source Increase Gas Exchange, Grain Yield and Economic Viability in Common Bean - de Andrade, Aline Franciel; Bueno, Amanda Magalhães; de Carvalho, Aline dos Santos; de Lima, Mateus Leles; Flores, Rilner Alves; de Oliveira Abdala, Klaus; de Mello Prado, Renato [UNESP]; de Souza Junior, Jonas Pereira [UNESP] (Springer Nature, 2021)
Purpose: New soluble sources of silicon (Si) have arrived in the agribusiness. Some of them are being considered efficient by their used composition, improving absorption of this beneficial element, photosynthetic parameters, and yield. However, the economic feasibility of using this source must be considered. Thus, the present study aimed to evaluate the effect of the foliar application of increasing concentrations of Si on the physiological aspects grain yield in common bean and the economic viability of silicon application. Methods: Randomized block design with seven Si concentrations: 0.00, 0.33, 0.66, 1.00, 1.33, 1.66 and 2.00 g L− 1. Solutions were applied via foliar spraying covering the whole treatment area. Solutions were provided in triplicates and three different days after sowing (40, 55, and 70 DAS). Si accumulation, gas exchange (stomatal conductance, transpiration, photosynthesis, and internal CO2 concentration), photochemical efficiency, productivity, and economic viability were evaluated. Results and conclusions: Foliar applications of Si as sodium and potassium silicate stabilized with sorbitol were found to be efficient in providing Si for bean cultivation. The beneficial effect of Si application in the photosynthetic and yield parameters was observed in this study. However, when Si concentration is higher than 1.16 g L− 1 it is considered not economically viable.
Keywords: Beneficial element; Economic viability of silicon application; Phaseolus vulgaris; Photosynthesis; Plant nutrition